Drag reduction in ducts using structured internal surfaces - Al-Hashem, Hassan Dhiaaldeen Mahammed (2017)
Enhancing the flow of submerged surfaces as in pipeline, submarines, ships, and even airplanes attracted enormous numbers of researchers in the past few decades. A huge amount of energy has spent to overcome the drag force which results in a loss in energy. Several techniques were conducted to find the possible way to enhance the flow of submerged surfaces. Currently the most popular method for reducing drag employed the use of additives (active means). However, these active means do have drawbacks such as mechanical degradation, altering the chemical and physical properties of the fluid they inhabit as well as being toxic and non-biodegradable for the most part and many extra stages must be included to ensure that an additive is suitable. As a result, the additive increases costs and reverses savings. This has spurred new research aimed to explore more nature-friendly, non-additive means of drag reduction. In the present study, two sets of riblets we designed and fabricated, the sets classified according to groove according to orientations (longitudinal and transverse) riblets both sets contain five subsets of five riblet shapes (triangular, trapezoidal, spaced triangular, L-groove, and U-groove). Each riblet shape had heights of 600, 800 and 1000 μm, with varied spacing so that the resultant protrusions into the flow remained similar to provide an accurate comparison of the effects of riblets on turbulent flow in a closed loop channel flow system with different operating conditions. The velocity distribution over the investigated surfaces was determined using mini-LDV system. The experimental data showed that the percentage drag reduction (%DR) was higher and more efficient when the direction of flow over the structured surfaces is longitudinal. Increasing the riblets height led to a decrease in the %DR reported. The experimental results showed that the U-groove riblets had the highest %DR values with maximum flow enhancement of 13.7% observed in 600 ×750 μm design. The pressure drop measurements of the present work gave a clear indication and mapping of the flow behavior over the investigated surfaces, where reductions in the pressure drop readings are spotted with almost consistent time periods and that is a clear indication of the creation and bursting of turbulence structures over the surfaces when the structure of the surface is changed. The mini-LDV velocity distribution reveals the fact that the flow behavior over the rib surfaces changes completely when compared to the smooth surface. The velocity values of the rib surfaces were lower than that of the smooth surfaces when the laser measurements were 1 mm from the surface, and it became much higher than the values of the smooth surfaces when it reaches its maximum measurement point (25 mm above the surface). Such finding supports the idea of redirecting the turbulence towards the center of the duct where the degree of turbulence became higher. Finally as a conclusion, it was found that the geometry dimensions can massively control the drag reduction effect even if the direction of flow is transverse where certain drag reduction effects can be measured.